Effect of solids on O₂ mass transfer in an oscillatory flow reactor provided with smooth periodic constrictions - Ferreira, A. (2017)
n the present work, it is studied for the first time the use of an oscillatory flow reactor provided with smooth period constrictions (OFR-SPC) in gas-liquid mass transfer process when a solid phase is present. The superficial gas velocities (uGuG), solids loading (calcium alginate beads: 0-15% (v/v)) and the oscillatory conditions (frequency and amplitude) effects on volumetric liquid side mass transfer coefficient (kLakLa) are experimentally evaluated. The liquid-side mass transfer coefficient, kLkL, and the specific interfacial area, a  , are studied individually. The results show that kLakLa increases with both superficial gas velocity and oscillatory conditions, in two and three-phase systems, the oscillatory conditions being the ones with the highest impact on the gas-liquid mass transfer process. The presence of solids seems to have a negligible influence on kLakLa in all experimental conditions for the range of solids loading studied. This behaviour was not observed in other reactors where a negative solids (calcium alginate beads) influence on the mass transfer process was verified. Globally, the results show the importance of hydrodynamic phenomena on the mass transfer process in two and three-phase systems, indicating OFR-SPC as a good alternative to the conventional reactors, especially when a third phase is present.